Differential response to intracellular stress in the skin from osteogenesis imperfecta Brtl mice with lethal and non lethal phenotype: A proteomic approach() - Bianchi, Laura (J Proteomics, 2012)
Phenotypic variability in the presence of an identical molecular defect is a recurrent feature in heritable disorders and it was also reported in osteogenesis imperfecta (OI). OI is a prototype for skeletal dysplasias mainly caused by mutations in the two genes coding for type I collagen. No definitive cure is available for this disorder, but the understanding of molecular basis in OI phenotypic modulation will have a pivotal role in identifying possible targets to develop novel drug therapy. We used a functional proteomic approach to address the study of phenotypic variability using the skin of the OI murine model Brtl. Brtl mice reproduce the molecular defect, dominant transmission and phenotypic variability of human OI patients. In the presence of a Gly349Cys substitution in α1(I)-collagen Brtl mice can have a lethal or a moderately severe outcome. Differential expression of chaperones, proteasomal subunits, metabolic enzymes, and proteins related to cellular fate demonstrated that a different ability to adapt to cellular stress distinguished mutant from wild-type mice and mutant lethal from surviving mutant animals. Interestingly, class discovery analysis identified clusters of differentially expressed proteins associated with a specific outcome, and functional analysis contributed to a deeper investigation into biochemical and cellular pathways affected by the disease. This article is part of a Special Issue entitled: Translational Proteomics.